PENGARUH UPAH MINIMUM TERHADAP TINGKAT PRODUKTIVITAS KERJA PT. TELKOM CABANG BOGOR - Rini Ardista (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
This research aims to determine whether the minimum wage is related to the level of work productivity of the production department at PT. TELKOM CABANG BOGOR, to find out whether the minimum wage affects the work productivity of the employees of PT. TELKOM CABANG BOGOR. The sample used was 100 respondents taken by accidental sampling technique in the PT. TELKOM CABANG BOGOR. This research uses simple linear regression. A tool to measure it is assisted by SPSS version 22. The results of the linearity test of the effect of the minimum wage on work productivity, there is a significance value of 0.115 which is greater than 0.05, so there is a linear relationship. The results of the t test show that the minimum wage has a significance level of 0.115 and the t value of 3.345> t table of 1.984 is greater than 0.05. From the results of the F test it can also be concluded that the F-table at df1 = 2 df2 = 97 is obtained from the F distribution table of 3.09 at the 95% confidence level (Alpha = 5%). This proves that Fcount (88,986)> from Ftable (3.09), while the significance (0,000) <from alpha is at the 95% confidence level (Alpha 5%). So that Ha which says there is a significant influence between the minimum wage on the work productivity of the production section at PT. TELKOM CABANG BOGOR accepted. While Ho, which says there is no significant effect between minimum wages on work productivity at PT. TELKOM CABANG BOGOR rejected.